Associations among cervical dilatation at admission, intrapartum care, and birth mode in low‐risk, nulliparous women. Issue 2 (28th January 2019) - Iobst, Stacey E.; Breman, Rachel B.; Bingham, Debra; Storr, Carla L.; Zhu, Shijun; Johantgen, Meg
Abstract: Background: Admission in early labor is associated with increased likelihood of cesarean birth, but the context in which this occurs is unclear. Previous research has explored the relationship between dilatation at admission and the use of single intrapartum interventions; however, the majority of women in the United States receive multiple intrapartum interventions. The objective of this study was to examine the associations among cervical dilatation at admission, intrapartum care, and birth mode in low‐risk, nulliparous women with spontaneous onset of labor. Methods: This was a cross‐sectional, observational study of 21 858 nulliparous, singleton, term vertex births that occurred from 2002 to 2007 across nine hospitals in the Consortium on Safe Labor. Outcome measures included the individual and combined use of intrapartum interventions (amniotomy, epidural anesthesia, oxytocin augmentation) and birth mode. Results: In this sample, 92.0% of women received at least one intrapartum intervention and 22.7% received all three interventions. After propensity score adjustment, women were more than twice as likely to receive the combination of amniotomy‐epidural‐oxytocin when admitted at 0‐3 cm (RR 2.83 [95% CI 2.45‐3.27]) and 4‐5 cm (2.49 [2.15‐2.89]) compared to 6‐10 cm. Adjusted likelihood of cesarean birth was five times greater for women admitted at 0‐3 cm (5.26 [4.36‐6.34]) and two times greater for women admitted at 4‐5 cm (2.27 [1.86‐2.77]) compared to 6‐10 cm. Conclusions: To promote normal physiologic birth, low‐risk, nulliparous women should be engaged in shared decision‐making about timing of admission after spontaneous onset of labor.